Development of immune-modulatory RNAS to regulate RIG-I-like receptors mediated antiviral immune response for therapy and vaccination - Yong, Hui Yee (2019)
Retinoic Acid-Inducible Gene I (RIG-I) is a cytosolic pattern recognition receptor (PRR) involved in initiating host defence response against viruses. RIG-I distinguishes between self and foreign nucleic acids by recognising chemical features not found in endogenous cytoplasmic RNA. RIG-I exhibits a high affinity binding for blunt ended duplex RNA terminus containing a 5’ triphosphate moiety. In this thesis, the development of potent innate immune modulatory RNA (ImmRNA), capable of triggering a robust type I interferon signalling in human cells is reported. Several short hairpin RNAs terminated at one end with a stable UUCG tetraloop and the other with 5’ triphosphate were designed. From these hairpin dsRNAs, the shortest hairpin required to activate type I interferon signalling is the RNA with 10 perfectly base paired stem RNA (3p10L). From these findings, mismatch along the stem of the RNA was introduced to create a guanosine insertion along the stem of the 3p10L RNA and enhanced type I interferon signalling in both HEK-Lucia™ RIG-I cells and THP1-Dual™ with the guanosine insertion at the position 9 of 3p10L (3p10LG9) were observed. Conformational dynamics studies via HDX-MS of human RIG-I bound to 3p10LG9 revealed that the overall binding of CTD and HEL1 domain was tighter to 3p10LG9 as compared to 3p10L. Next, the encapsulation of ImmRNAs into virus-like particles (VLP) was carried out. The coat protein for two different RNA bacteriophage, MS2 and Q beta were cloned and recombinantly expressed in E.coli. A spontaneously formed VLP from both MS2 and Q beta were obtained after several purification steps and was confirmed via negative staining Electron microscopy. Furthermore, coat protein for Q beta was also purified and assembled with the immRNA into Q beta VLP. Altogether, the work in this thesis provides insights into the development of robust innate immune modulatory RNAs as agonists of RIG-I and the development of potential delivery tools for ImmRNAs.